Unconscious perception by athletes of negative incentives associated with competitive activity - Golub, Ya. V.; Ageev, E. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the influence of late evoked potentials N200, P300 on the unconscious perception of negative stimuli, using the example of words associated with competitive activity in conditions of disguise using the example of martial arts.